Copper(I)–creatine complex on magnetic nanoparticles as a green catalyst for N‐ and O‐arylation in deep eutectic solvent. (14th January 2020) - Bagheri, Sepideh; Pazoki, Farzane; Radfar, Iman; Heydari, Akbar
Abstract : Immobilization of copper(I) ions on magnetic nanoparticles was performed using surface modification of Fe3 O4 with creatine. Fe3 O4 @creatine‐Cu(I) magnetic catalyst was synthesized and applied in C&bond;X cross‐coupling reactions with aryl halides in a deep eutectic as a green solvent. The results indicate the Fe3 O4 @creatine‐Cu(I) magnetic nanoparticles showed excellent activity and high stability. In addition, it was revealed that this catalyst can be recycled five times without significant loss in catalytic activity. Abstract : Fe3 O4 @creatine‐Cu(I) was synthesized using surface modification of Fe3 O4 with creatine. The Fe3 O4 @creatine‐Cu(I) magnetic catalyst was applied for C&bond;X cross‐coupling reactions with aryl halides in a deep eutectic as a green solvent. The magnetic nanoparticles showed excellent catalytic activity.